Listening to/with Mar Paradoxo: a collective practice for sharing listenings - Germano, Gustavo Branco; Marino, Alexandre; Tápia, Daniel; Lima, Henrique Rocha de Souza; Campesato, Lílian; Ferreira, Marina Mapurunga de Miranda da; Bonafé, Valéria; Reis, Vicente (Revista Vórtex, 2021)
This paper presents an experimental methodology developed by the collective Laura: Place for Research on Aurality for approaching listening as a shared experience. As a motif for the application of this methodology, we take the work Mar Paradoxo (Raquel Stolf, 2016) as a proposition for experiencing multiple modes of listening. To contextualize our understanding of Stolf’s work, we refer to the concept of otography as a way of approaching the listening experience as something that makes and is made out of traces. By means of the production, sharing, and analysis of listening reports, we outline different modes through which our listening navigates. These modes help us understand listening as an experience that is multi-mediated and relational, singular and situated. In the end, we emphasize the presence of the other in the listening subject, resonating the thesis that the listening activity is driven by a desire of making one’s listening listened.